Triphora albanoi Bakker & Swinnen 2021 ... - Bakker, Piet A. J.; Albano, Paolo G. (Zenodo, 2022)
Triphora albanoi Bakker & Swinnen, 2021 Triphora albanoi Bakker & Swinnen, 2021: 137, fig. 6. Type locality. Ascension Island, Boatswain Bird Island, 13 m, 07°53’09.2”S, 14°18’50.0”W. Type material. RBINS I.G. 34360 MT.3900, holotype. Distribution. Ascension Island (Bakker & Swinnen 2021). ... : Published as part of Bakker, Piet A. J. & Albano, Paolo G., 2022, Nomenclator, geographic and stratigraphic distribution of the family Triphoridae (Mollusca: Gastropoda), pp. 1-216 in Zootaxa 5088 (1) on page 20, DOI: 10.11646/zootaxa.5088.1.1, http://zenodo.org/record/5836536 ...